Trends in Corruption Reporting in State-Owned Enterprises and Ministry Institutions in Indonesia 2020-2024 - Pratiwi, Nahya Yuliani; Astrianingsih, Gita; Sabrina Maharani, Farhah Novia; Kirani, Nurfadilla Alya; Anggraeni, Rifa; Wardani Widodo, Anis Kusuma (Riviera Publishing, 2025)
This study aims to identify trends in reporting on corruption cases in state-owned enterprises (BUMN) and ministries in Kompas Daily during the 2020–2024 period. The method used was quantitative content analysis with a sample of 250 news items selected using probability sampling (simple random sampling). This study covers the institutions most frequently involved, the types of corruption that occur, the positions of the perpetrators, the modus operandi, and the amount of state losses. The analysis results show that ministries are the institutions most frequently reported on for corruption (59%), while state-owned enterprises (BUMN) are in second place (41%). Overall, these findings indicate that the problem of corruption in both institutions is inseparable from weak internal oversight, high centralization of authority, and governance vulnerabilities. This study emphasizes the importance of strengthening transparency, accountability, and public control in efforts to prevent and eradicate corruption.